PROTAGONIST’S LOYALTY IN SIDNEY SHELDON’S NOVEL TELL ME YOUR DREAMS - Pardi Pardi; Yuis Novellia Ardescy (Universitas Islam Sumatera Utara, 2022)
The aim of this study is to analyze the kinds of protagonist’s loyalty in Sidney Sheldon’s novel Tell Me Your Dreams. The theory applied in this research is the one proposed by Fletcher, in which it is stated that loyalty emerges when someone has a feeling to protect something.The data are taken from the novel by using descriptive analysis method. The method used is qualitative. The results show that there are two kinds of protagonist’s loyalty found in the novel. They are loyalty to his mother and loyalty to his friend. Loyalty or being loyal to his mother is shown by the protagonist by a commitment he makes as a deal with his allegiance to save her mother; meanwhile, being loyal to his friend is shown by the protagonist by fulfilling his commitment to help his friend in trouble. Being a loyal person will give the person positive effect in family, in workplace or in society. He will be a trust-worthy person and a place for someone to lean on.